If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -3x + -5 = x Reorder the terms: -5 + 4x + -3x = x Combine like terms: 4x + -3x = 1x -5 + 1x = x Solving -5 + 1x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -5 + 1x + -1x = x + -1x Combine like terms: 1x + -1x = 0 -5 + 0 = x + -1x -5 = x + -1x Combine like terms: x + -1x = 0 -5 = 0 Add '5' to each side of the equation. -5 + 5 = 0 + 5 Combine like terms: -5 + 5 = 0 0 = 0 + 5 Combine like terms: 0 + 5 = 5 0 = 5 Simplifying 0 = 5 Combine like terms: 0 + -5 = -5 -5 = 5 + -5 Combine like terms: 5 + -5 = 0 -5 = 0 The solution to this equation could not be determined.
| 0.04n=7.2 | | 5(-3x-3)=120 | | 79-2x=16x+15 | | ln*(x-22)=39 | | -2(4y+6)= | | 2x+1=4+4x-3 | | 3.15=15y | | 3=-3n-(-5n+1) | | 2+8x=4(2x+2)-6 | | -4k=9k | | -5h=-32/3 | | 16x^2-88x+121=0 | | -1x+4=7x-3 | | 8x-73=4x-9 | | 6a-5(8-3a)= | | 4k-8k=-6 | | 38-n=4.7 | | 60=-5r | | 2+4n+7=21 | | 6-8x=98-36x | | 15x=-240 | | 0.12x-0.65=1.28 | | .13-.01(x+1)=-.03(4-x) | | 12(3x+5)-6(2x-2)=4x-68 | | 2x+7=17-10x | | 16-8t=5-9t | | 0.75x+3.22=6.97 | | 1x+4=7x-3 | | 2(x+4)-3=4x-2(-5+x) | | 112-4x=4x-24 | | y+5(y-1)=7 | | (5x-2)(2x)=115 |